The therapeutic effects of attending a one-day outpatient service on patients with gestational diabetes and different pre-pregnancy body mass indices - Cao, Yan-Min; Ma, Min; Wang, Wei; Cai, Na-Na (Frontiers in Public Health, 2023)
Purpose This study investigated the effects of attending a one-day outpatient service on the outcomes of patients with gestational diabetes mellitus (GDM) and different pre-pregnancy body mass indices (BMIs). Methods The study recruited 311 pregnant women with GDM into a one-day outpatient service at The Fourth Hospital of Shijiazhuang from September 2019 to December 2021. They were randomly assigned to three groups, based on their pre-pregnancy BMI as follows: group A, BMI < 18.5 kg/m2; group B, 18.5 ≥ BMI > 25.0 kg/m2; group C, BMI ≥25 kg/m2. The following information was collected from all the participants: fasting blood glucose, hemoglobin A1c (HbA1C), insulin dose, gestational weight gain, weight gain after the one-day outpatient service, and perinatal outcomes. Results The three groups showed significant differences in fasting blood glucose and HbA1C, insulin treatment rate, and the incidence of pregnancy hypertension/preeclampsia and neonatal jaundice (all P < 0.05). The rate of excessive gestational weight gain in all of the groups also reflected significant differences (P < 0.05). Group A showed the lowest weight gain, while group C gained the most weight. There is no significant difference in the incidences of hypertension/preeclampsia, neonatal jaundice, or premature birth between patients with weight loss/no weight gain and those with positive weight gain. Conclusion One-day diabetes outpatient integrated management may effectively help to manage weight gain and blood glucose in patients with GDM and different pre-pregnancy BMIs. Dietary control after a GDM diagnosis may have helped to avoid weight gain entirely, as well as negative weight gain, but did not increase the risk of maternal and infant-related complications.